Why do paramedics choose to bring patients to a private emergency department?. (22nd July 2018) - Aldridge, Emogene S; Lim, Anthony; Rogers, Ian R; Hicks, Brontie; Bailey, Paul M
Abstract: Objective: While prior experience, favourable location and anticipation of high quality care are known to influence patient choice to attend a private ED, it is likely that decision‐making is also influenced by other persons. In particular, patients arriving by ambulance are under the care of paramedics, whose values towards healthcare and rationale for choosing one ED over another have not been studied. This study aimed to describe reasons why paramedics choose to bring patients to a private ED. Methods: Exploratory, qualitative study using semi‐structured, face‐to‐face interviews with paramedics bringing patients to a private ED from the community. Two primary questions reinforced by structured prompts were asked: 'Why did you choose to come to this emergency department?' and 'What are your general expectations of this emergency department visit?' Interviews were audio recorded, transcribed verbatim and analysed thematically. Results: Fifty paramedics were interviewed with 48 interviews able to be transcribed and used in analysis. Four factors were identified to increase the likelihood of a private ED destination: specific direction, institutional allegiance, hospital logistics and systems and receiving hospital service ethos. Conclusions: Paramedics take into consideration when possible patient's wishes and are more likely to bring a patient to a private ED if they have specific direction from the patient or the patient's family or GP. The likelihood of presenting to a private ED is increased if the patient has an allegiance with the facility and the paramedics perceive favourably the hospital logistics and systems as well as service ethos.